Percentage Level of Tannin fur Rabbit for Leather Concerning Stitch Tearing Strength, Tearing Strength and Flexibility - Mustakim Mustakim; Aris Sri Widati; Lisa Purnaningtyas (Faculty of Animal Science Universitas Brawijaya, 2007)
The purpose of this study was to find out the appropriate of tannin level for rabbit fur leather concerning stitch tearing strength, tearing strength, and flexibility. The result were expected to contribute good information for the society, leather craftsman, and further researchers about fur leather tanning especially rabbit fur leather with tannin concerning stitch tearing strength, tearing strength and flexibility. The material that used were 12 pieces of four months of rabbit skin. The research method was Completely Randomized Design, consist of three treatments of tannin, they were: M1 (mimosa 15%), M2 (mimosa 20%), and M3 (mimosa 25%). Each of treatment hold on four repetition, the variables which measured were stitch tearing strength, tearing strength, and flexibility of fur leather. Data were analysed by analysis variance followed by Duncan’s Multiple Range Test. The result of this research indicate that the use level of tannin give significant influence (P<0.05) among stitch tearing strength, tearing strength. It gave a very significant influence (P<0.01) for flexibility of rabbit fur leather. Based on the result, can be concluded that 25 % of tannin (mimosa), produce the best result on stitch tearing strength and tearing strength. The increase of tannin offer will decrease the flexibility of fur leather but the lowest tannin produced the best flexibility of fur leather (15 percent). The best quality of rabbit fur leather produced by 25 % of tannin. Keywords : leather, tannin, quality